Pathophysiology of visual disorders induced by phosphodiesterase inhibitors in the treatment of erectile dysfunction - Moschos MM; Nitoda E (Dove Medical Press, 2016)
Marilita M Moschos, Eirini Nitoda 1st Department of Ophthalmology, Medical School, National & Kapodistrian University of Athens, Athens, Greece Aim: The aim of this review was to summarize the ocular action of the most common phosphodiesterase (PDE) inhibitors used for the treatment of erectile dysfunction and the subsequent visual disorders.Method: This is a literature review of several important articles focusing on the pathophysiology of visual disorders induced by PDE inhibitors.Results: PDE inhibitors have been associated with ocular side effects, including changes in color vision and light perception, blurred vision, transient alterations in electroretinogram (ERG), conjunctival hyperemia, ocular pain, and photophobia. Sildenafil and tadalafil may induce reversible increase in intraocular pressure and be involved in the development of nonarteritic ischemic optic neuropathy. Reversible idiopathic serous macular detachment, central serous chorioretinopathy, and ERG disturbances have been related to the significant impact of sildenafil and tadalafil on retinal perfusion.Discussion: So far, PDE inhibitors do not seem to cause permanent toxic effects on chorioretinal tissue and photoreceptors. However, physicians should write down any visual symptom observed during PDE treatment and refer the patients to ophthalmologists. Keywords: erectile dysfunction, pathophysiological mechanisms, phosphodiesterase inhibitors, PDE5, visual disorders